Explorating the synthesis of quaternary salts of a tetraaryl substituted imidazole as ionic liquids precursor - Pérez-Méndez, Maricela; Ferrer-Serrano, Armando; Rojas-Vargas, Julio A.; García-López, América (Revista Cubana de Química, 2023)
Ionic liquids are compounds that have a large number of properties and applications in environmentally friendly processes. In the present research an exploratory study of the synthesis of quaternary salts of tetraaryl imidazoles substituted as an initial step towards the synthesis of ionic liquids was carried out. A tetraaryl imidazoles was synthesized using the H3BO3/ethylene glycol catalyst system. The 1-(3-methylphenyl)-2-(4-nitrophenyl)-4,5-diphenylimidazole obtained was used to perform the quaternization reaction with butyl bromide, using purification criteria as thin layer chromatography (TLC), melting temperature and as a characterization criterion for electrospray mass spectrometry.